A literature review of air mixing devices for psychrometric performance measurement applications (ASHRAE RP-1733). (2nd July 2020) - Park, H.; Bach, C. K.
Abstract : For measurements of unitary HVAC&R equipment and heat exchanger performance, tolerances on capacity measurements relative to the published ratings or mismatch in energy balances are limited to 5% as mentioned in AHRI standards (210/240, 340/360, and 365), ASHRAE 33 and 37, and in U.S. federal regulations. However, differences in design of the air mixing and measuring apparatus due to generous guidelines may result in discrepancies in measured airside capacity that exceed the allowable tolerances, leading to so-called "false testing failures." In order to maintain the HVAC&R industries' credibility, it is essential to develop standardized design criteria for the test apparatus that reduce the probability of such failures. This literature review gives an overview of available and relevant research and standards to provide comprehensive and general information on air mixing devices and measurement techniques for psychrometric performance testing. Furthermore, this review article summarizes mixing effectiveness and static pressure drop for representative mixer types, design parameters, and various testing conditions based on our understanding of experimental results in open literature.